Control of Common Groundsel in Florida Container Nurseries - Alejandro Bolques; Jeffrey G. Norcini; James Aldrich; Courtney E. Gist (EDIS)
Common groundsel (Senecio vulgaris L.) is a weed that needs to be monitored year-round in container nurseries since these conditions are ideal for common groundsel. Seed can germinate only a few days after they land on the container medium surface (Figure 1). This document is ENH980, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2004.